Assessment of left ventricular function using the Myocardial Performance Index in term fetuses that develop intrapartum compromise. (18th April 2019) - Alsolai, Amal A.; Bligh, Larissa N.; Greer, Ristan M.; Gooi, Alexander; Kumar, Sailesh
Abstract: Objective: To investigate the relationship between the prelabour left ventricular Myocardial Performance Index (LVMPI) and intrapartum fetal compromise (IFC) in low-risk term pregnancies. Methods: A blinded, prospective observational cohort study at the Mater Mother's Hospital, Brisbane, Australia. A cohort of 284 women with uncomplicated singleton pregnancies underwent fortnightly ultrasound from 36 weeks until delivery. The LVMPI was assessed by conventional Doppler ultrasound and correlated with intrapartum outcomes. The LVMPI was also correlated with other Doppler indices of fetal wellbeing. Results: Two hundred and seventy-three women were included in the final analysis, the median LVMPI was higher in fetuses that required any emergency operative delivery for IFC (0.56, 0.52–0.60 versus 0.54, 0.50–0.58, p  = .007). The left ventricular cardiac output (LVCO) and cerebroplacental ratio (CPR) were lower in fetuses that required any emergency operative delivery for IFC compared to those that did not (164 ± 19 ml/min/kg versus 181 ± 30 ml/min/kg, p  < .001) (1.63 + 0.30 versus 1.90 + 0.50, p  < .001), respectively. The LVMPI was inversely correlated with the CPR ( r  = −0.20, p  < .01), MCA PI ( r  = −0.29, p  < .01), and LVCO ( r  = −0.22, p  < .01). Conclusions: Higher global LVMPI is associated with a higher risk for IFC and poorer condition of the newborn.